Research on public management efficiency improvement method based on parallel database oriented optimization management information system - Han, Yingjun; Sun, Rui (RISTI : Revista Ibérica de Sistemas e Tecnologias de Informação, 2016)
In recent years, with the rapid and bursting development of manage information system and the data base technology, the applications have been varying from general science and social science applications. Under this condition, this paper proposes the novel public management efficiency improvement method based on the parallel database oriented optimization management information system. The history of the public administration paradigm shift shows that the task of public management and the form is always the certain historical period of the development level of productivity and the production organization form of the decision and restriction. Public administration is to provide public goods to the society. With the MIS and DB theory, we can improve the mode as these aspects which are reflected from the MIS architecture optimization. (1) Loose coupling of the Web Services directly from loose coupling business elements, elements of our business in the design business process must be separated from business elements. (2) OA is cross-platform, not be restricted by using any language and operating system, but to the upper open API interface that provide the basic algorithm. (3) With the data layer support, the implementation services for the entire system provide a solid foundation. The quantitative analysis has been conducted to verify the systematic effectiveness. Keywords: Public management, Efficiency, Improvement method, Parallel database, Management information system, Optimization